Straightforward synthesis of 2- and 2,8-substituted tetracenes - Woodward, Simon; Ackermann, Miriam; Ahirwar, Saurabh; Burroughs, Laurence; Robert Garrett, Mary; Ritchie, John; Shine, Jonathan; Tyril, Bjork; Simpson, Kevin; Woodward, Peter (Wiley-VCH Verlag, 2017)
A simple regiospecific route to otherwise problematic substituted tetracenes is described. The diverse cores (E)- 1,2-Ar1CH2(HOCH2)C=C(CH2OH)I (Ar1 = Ph, 4-MePh, 4-MeOPh, 4-FPh) and (E)-1,2-I(HOCH2)C=C(CH2OH)I, accessed from ultra-low cost HOCH2C≡CCH2OH at multi-gram scales, allow the synthesis of diol libraries (E)-1,2- Ar1CH2(HOCH2)C=C(CH2OH)CH2Ar2 (Ar2 = Ph, 4-MePh, 4-iPrPh, 4-MeOPh, 4-FPh, 4-BrPh, 4-biphenyl, 4-styryl; 14 examples) by efficient Negishi coupling. Copper-catalysed aerobic oxidation cleanly provides dialdehydes (E)-1,2- Ar1CH2(CHO)C=C(CHO)CH2Ar2 which in many cases undergo titanium(IV) chloride induced double Bradsher closure providing a convenient method for the synthesis of regiochemically and analytically pure tetracenes (12 examples). The sequence is typically chromatography-free, scalable, efficient and technically simple to carry out.